2019
DOI: 10.3389/fpsyg.2019.00662
|View full text |Cite
|
Sign up to set email alerts
|

Being Bullied at School: Gratitude as Potential Protective Factor for Suicide Risk in Adolescents

Abstract: Bullying victimization has been recognized as a risk factor for social, physical, and psychological problems in adolescence. One promising resource that seems to protect adolescents from adversity and traumatic events is gratitude. However, no analysis of the specific role of gratitude in bullying context has been performed as yet. Thus, the aim of this research was to explore the associations between bullying victimization, gratitude and suicide risk (i.e., depressive symptoms and suicidal thoughts and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 73 publications
7
43
1
3
Order By: Relevance
“…Prior studies have also shown that gratitude has a positive impact on adolescent happiness, as it involves reflection, positive emotions, adaptive social behaviors, and relationships that facilitate well-being (Fredrickson, 2004;Watkins, 2004;Armenta et al, 2017). In fact, it has been reported that people with higher levels of gratitude experience less anger, feelings of loneliness, and fewer depressive symptoms (Breen et al, 2010;Wu et al, 2018;Rey et al, 2019).…”
Section: Virtues (Gratitude and Forgiveness)mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have also shown that gratitude has a positive impact on adolescent happiness, as it involves reflection, positive emotions, adaptive social behaviors, and relationships that facilitate well-being (Fredrickson, 2004;Watkins, 2004;Armenta et al, 2017). In fact, it has been reported that people with higher levels of gratitude experience less anger, feelings of loneliness, and fewer depressive symptoms (Breen et al, 2010;Wu et al, 2018;Rey et al, 2019).…”
Section: Virtues (Gratitude and Forgiveness)mentioning
confidence: 99%
“…While recent studies show that gratitude and forgiveness have the twofold benefit of decreasing the risk of aggression and victimization and also reducing the negative consequences of being bullied (Karremans et al, 2005;Egan and Todorov, 2009;Riek and DeWit, 2018;Rey et al, 2019;Yu and Chan, 2019), little is known about their relations with bystander behavior.…”
Section: Virtues (Gratitude and Forgiveness)mentioning
confidence: 99%
“… Li et al (2012) investigated the suicide risk of 1,252 Chinese middle school students from Guangzhou and found that gratitude can significantly reduce the suicide risk of teenagers. Similarly, Rey et al (2019) focused on school bullying among high school students and explored the causes of suicidal behavior among adolescents in the context of trauma. They found that gratitude is an important protective factor for suicidal behavior in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars suggest that gratitude has a positive relationship with wellbeing [ 52 , 53 ]. It also has been reported that people with greater levels of gratitude have fewer negative emotions [ 54 , 55 ] and more prosocial behavior [ 56 , 57 ]. A number of studies have shown that gratitude is associated with positive interpersonal relationships and social outcomes; however, it still remains unclear how gratitude influences negative and violent behaviors [ 58 ].…”
Section: Introductionmentioning
confidence: 99%